Plasmonic–perovskite solar cells, light emitters, and sensors - Ai, Bin; Fan, Ziwei; Wong, Zi Jing (Microsystems & nanoengineering, 2022)
The field of plasmonics explores the interaction between light and metallic micro/nanostructures and films. The collective oscillation of free electrons on metallic surfaces enables subwavelength optical confinement and enhanced light–matter interactions. In optoelectronics, perovskite materials are particularly attractive due to their excellent absorption, emission, and carrier transport properties, which lead to the improved performance of solar cells, light-emitting diodes (LEDs), lasers, photodetectors, and sensors. When perovskite materials are coupled with plasmonic structures, the device performance significantly improves owing to strong near-field and far-field optical enhancements, as well as the plasmoelectric effect. Here, we review recent theoretical and experimental works on plasmonic perovskite solar cells, light emitters, and sensors. The underlying physical mechanisms, design routes, device performances, and optimization strategies are summarized. This review also lays out challenges and future directions for the plasmonic perovskite research field toward next-generation optoelectronic technologies.